PERBANDINGAN EFEKTIVITAS KOMPRES SERAI DAN KOMPRES JAHE GAJAH TERHADAP NYERI SENDI LANSIA - Untari Tejawati; Erwin Erwin; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Symptoms of joint pain is usually experienced by ederly who have changed in musculosceletal system. This purpose of this study is to determine comparison in effectiveness of lemongrass and elephant ginger compresses to reduce joint pain. This study used pre-experimental research, with a comparative approach on “One group pre-test-post-test design”; conducted at Tresna Werdha Khusnul Khotimah nursing home, Pekanbaru, with 22 person as participants. Data were collected using Numeric Rating Scale (NRS). The implementation from those three kinds of compresses was done for 20 minutes in 3 days. The results of dependent t test lemongrass compress with p value 0.000 < α (0,05) and elephant ginger compress with p value 0,000 < α (0,05). The results of independent t test lemongrass and elephant ginger compress with value 0,010 < α (0,05). The study concluded that lemongrass compress and elephant ginger compress was efective for reducing joint paint, but compressing elepent ginger is more effective in reducing elderly joint paint. Keywords: Elephant Ginger Compress, Joint Pain, Lemongrass Compress